Exposure-Response of Palonosetron for Prevention of Chemotherapy-Induced Nausea and Vomiting in Pediatric Patients. Issue 4 (October 2016) - Wang, Jian; Mehrotra, Nitin; Kim, Insook; Lee, Sue-Chih; Sohrabi, Farrokh; He, Ruyi; Mulberg, Andrew; Sinha, Vikram; Ahn, Hae-Young; Bashaw, Dennis; Griebel, Donna
ABSTRACT: Objectives: Extrapolation of efficacy from adult populations to pediatrics may be appropriate if it is reasonable to assume that the 2 populations have similar disease progression and response to intervention. When full extrapolation of efficacy is deemed appropriate, the pediatric dose can be determined by "matching" exposure to a drug with that observed in adult patients. This approach has been used in certain therapeutic areas to alleviate the burden of pediatric clinical trials. We present here a case in which exposure matching is not appropriate. Methods: Data analyses including pharmacokinetics and exposure-response were performed using data obtained from 2 pediatric chemotherapy-induced nausea and vomiting trials for intravenously administered palonosetron (Aloxi; a 5-HT3 receptor antagonist) injection and the results were compared with adult findings. Results: At the approved doses for adults (0.25 mg) and pediatric patients (20 μg/kg), mean systemic exposure (area under the curve) of palonosetron in pediatric patients was approximately 3-fold higher than that in adults, whereas the response rate was similar between the 2 populations. Across pediatric patients, those younger than 6 years of age appeared to have a higher response than those ages 6 years or older, even though estimated systemic exposure was comparable between these age groups. Conclusions: Overall, these analyses provide an example in which pediatric and adult exposure data alone are insufficient to adequately identify effective pediatric doses and raise questions about the appropriateness of exposure matching for other drugs in the same therapeutic class. In such cases, pediatric dose-ranging and efficacy studies are needed.